Establishing a process of irradiating small animal brain using a CyberKnife and a microCT scanner. Issue 2 (17th January 2014) - Kim, Haksoo; Fabien, Jeffrey; Zheng, Yiran; Yuan, Jake; Brindle, James; Sloan, Andrew; Yao, Min; Lo, Simon; Wessels, Barry; Machtay, Mitchell; Welford, Scott; Sohn, Jason W.
Abstract : Purpose: : Establish and validate a process of accurately irradiating small animals using the CyberKnife G4 System (version 8.5) with treatment plans designed to irradiate a hemisphere of a mouse brain based on microCT scanner images. Methods: : These experiments consisted of four parts: (1) building a mouse phantom for intensity modulated radiotherapy (IMRT) quality assurance (QA), (2) proving usability of a microCT for treatment planning, (3) fabricating a small animal positioning system for use with the CyberKnifeˈs image guided radiotherapy (IGRT) system, and (4) in vivo verification of targeting accuracy. A set of solid water mouse phantoms was designed and fabricated, with radiochromic films (RCF) positioned in selected planes to measure delivered doses. After down‐sampling for treatment planning compatibility, a CT image set of a phantom was imported into the CyberKnife treatment planning system—MultiPlan (ver. 3.5.2). A 0.5 cm diameter sphere was contoured within the phantom to represent a hemispherical section of a mouse brain. A nude mouse was scanned in an alpha cradle using a microCT scanner (cone‐beam, 157 × 149 pixels slices, 0.2 mm longitudinal slice thickness). Based on the results of our positional accuracy study, a planning treatment volume (PTV) was created. A stereotactic body mold of the mouse was "printed" using a 3D printer laying UV curable acrylic plastic. Printer instructions were based on exported contours of the mouseˈs skin. Positional reproducibility in the mold was checked by measuring ten CT scans. To verify accurate dose delivery in vivo, six mice were irradiated in the mold with a 4 mm target contour and a 2 mm PTV margin to 3 Gy and sacrificed within 20 min to avoid DNA repair. The brain was sliced and stained for analysis. Results: : For the IMRT QA using a set of phantoms, the planned dose (6 Gy to the calculation point) was compared to the delivered dose measured via film and analyzed using Gamma analysis (3% and 3 mm). A passing rate of 99% was measured in areas of above 40% of the prescription dose. The final inverse treatment plan was comprised of 43 beams ranging from 5 to 12.5 mm in diameter (2.5 mm size increments are available up to 15 mm in diameter collimation). Using the Xsight Spine Tracking module, the CyberKnife system could not reliably identify and track the tiny mouse spine; however, the CyberKnife system could identify and track the fiducial markers on the 3D mold. In vivo positional accuracy analysis using the 3D mold generated a mean error of 1.41 mm ± 0.73 mm when fiducial markers were used for position tracking. Analysis of the dissected brain confirmed the ability to target the correct brain volume. Conclusions: : With the use of a stereotactic body mold with fiducial markers, microCT imaging, and resolution down‐sampling, the CyberKnife system can successfully perform small‐animal radiotherapy studies.